Towards Generative Didactics: mutations, expansions and co–agencies in more–than–human scenarios (Itinerarios Educativos, 2025)
This article explores, through the voices of teachers, emerging dynamics in education that arise at the intersection of didactics and generative artificial intelligence (GenAI) technologies. It examines how this assemblage produces mutations that transform not only teaching strategies but also power relations, the ontology of knowledge itself, and learning ecologies, reconfiguring traditional forms of knowledge. It discusses the implications of these mutations for rethinking teaching as a situated performance open to experimentation, and the ways in which GenAI challenges traditional regimes of veridiction.The article forms part of a qualitative and interpretive research project that is still in progress; its preliminary empirical work is developed based on teacher discourse within the framework of training experiences, workshops, and conferences. The corpus, comprising ethnographic records and audiovisual productions, is analyzed using Grounded Theory and an interdisciplinary theoretical framework, enabling both the generation of theory and the articulation of ethical and epistemological tensions that transcend adaptive logic. This configuration gives rise to a generative, experimental, and undisciplined didactic approach that unfolds through a dynamic and shared co–agency between humans and technologies.
Keywords: Generative didactics; generative expansions; Artificial Intelligence; didactic Mutations; teaching practices